Mechanically robust and thermally insulating polyarylene ether nitrile with a bone-like structure - Qing Qi; Jing Qin; Ruiyan Zhang; Shikai Luo; Xiaobo Liu; Chul B. Park; Yajie Lei (Materials & Design, 2020)
Inspired by the excellent mechanical performance of bone materials characterized by compact shell and porous core, this study proposes a lightweight, mechanically robust, and thermal-insulating polyarylene ether nitrile (PEN) with a bone-like structure. The supercritical fluid technique was applied to provide PEN with two types of tunable bone-like structures, which makes it simple to manipulated under supercritical treatment conditions. Depending on different bone-like microstructures, their tensile strength can reach up to 75 MPa with the impact strength range of 50–190 KJ/m2. Notably, the impact strength of PEN foam with a saturation time of 4 h is 1.6% higher than that of pure PEN. Furthermore, lightweight PEN foams capable of thermal insulation and their conductivity can reach 0.06 W/m.K without compromising the actual mechanical performance. These lightweight PENs with a remarkable performance in thermal insulation and mechanical robustness show a massive potential in automobile application for effectiveness in energy conservation and reducing air pollution. Based on this experiment, a new method is proposed to prepare biomimetic bone-like materials.